Prognostic Value of Serum Galectin-3 in Chronic Heart Failure: A Meta-Analysis - Cheng, Zhendong; Cai, Kefeng; Xu, Chaoxian; Zhan, Qiong; Xu, Xingbo; Xu, Dingli; Zeng, Qingchun (Frontiers in Cardiovascular Medicine, 2022)
Objective To evaluate the association between serum galectin-3 and all-cause death (ACD) and cardiovascular death (CVD) in patients with chronic heart failure (CHF). Methods The PubMed and Embase databases and Clinical Trials Registry (www.clinicaltrials.gov) were searched for studies with data on serum galectin-3 and ACD and CVD in CHF patients. The hazard ratios (HRs) of ACD and CVD were calculated and presented with 95% CIs. HRs were pooled using fixed effects or random effects models when appropriate. Sensitivity analysis, meta-regression and subgroup analysis were applied to find the origin of heterogeneity. Visual inspection of Begg's funnel plot and Egger's test were performed to assess the possibility publication bias. Results Pooled data included the results from 6,440 patients from 12 studies in the meta-analysis. Higher serum galectin-3 was associated with a higher risk of ACD (HR, 1.38; 95% CI, 1.14–1.67) and CVD (HR, 1.13; 95% CI, 1.02–1.25) in CHF patients. In the subgroup analyses, higher serum galectin-3 was associated with an increased risk of ACD in all subgroups. The pooled HR of the shorter follow-up group (1.78; 95% CI, 1.50–2.11) was significantly higher than the pooled HR of the longer follow-up group (1.15; 95% CI, 1.05–1.25). Sensitivity analysis of eliminating one study in each turn indicated that Koukoui et al.'s study had the largest influence on the risk of all-cause death. All-cause death publication bias was not detected (Pr>|z| = 0.35 for Begg's test and P>|t| = 0.15 for Egger's test). Conclusions Serum galectin-3 has prognostic value of both all-cause death and cardiovascular death in CHF. Serum galectin-3 could be useful for risk classification in patients with CHF. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=193399.